Uji Daya Hasil Padi Hibrida 172 dan 6 Pada Jarak Tanam yang Berbeda - Fitri Aprillia; Samanhudi Samanhudi; Bambang Pujiasmanto (Agrotechnology Research Journal, 2017)
Rice is the main commodity in food support, especially in Indonesian society. As a country with a large population, there are challenges in collecting the food needs of the population, the challenge is to improve the efficiency and optimizing the utilization of land resources. The purpose of this study is to determine the use of varieties / lines were superior and spacing are effective in increasing productivity. The research was conducted at the experimental land Faculty of Agriculture, Sebelas Maret University, Mojolaban, Sukoharjo. The research using Randomized Completely Block Design with 2 factors, namely rice varieties factor and plant spacing. Data were analyzed using analysis of variance and if there is a significant followed by DMRT (Duncan Multiple Range Test) at 5% level. 6 Chinese rice lines and spacing of 26 cm x 26 cm is a combination of treatments that have a higher level of productivity is 4.79 ton-1ha.